First record of the Indo-Pacific species Iphione muricata Savigny in Lamarck, 1818 (Polychaeta: Iphionidae) from the Mediterranean Sea, Israel - GOREN, L.; SHEFER, S.; FELDSTEIN, T. (Mediterranean Marine Science, 2017)
The Indo-Pacific scaleworm Iphione muricata was observed and caught in the Mediterranean Sea along the coast of Israel. Morphological and molecular diagnostic characters of the species are discussed. This is the first record of this alien species in the Mediterranean Sea, and its previous reports in the Suez Canal suggest its introduction via Lessepsian migration.